Prevalence of burnout and its associated factors among health care providers in health clinics in Kuantan during Covid-19 pandemic - Said, Abdul Hadi; Abd Rahman, Mohd Aizuddin; Tg Ariff @ Tg Zainuddin, Tg Puteri Syarizan; Yusof, Muhammad Zubir (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2024)
Introduction: Psychological exhaustion, disengagement, and diminished performance are the hallmarks of burnout. It can impact individuals engaged in employment involving interpersonal interactions, particularly in high-demand fields like healthcare. There exists a strong correlation between a significant degree of burnout among healthcare personnel and a notable decline in productivity. The purpose of the study is to examine the incidence of burnout and the related factors amidst the Covid-19 pandemic, among healthcare practitioners (HCP) working in governmental health clinics in Kuantan, Pahang, Malaysia. Materials and methods: From October 2021 to October 2022, a cross-sectional study of HCP who work at 14 government health clinics in Kuantan, Pahang, Malaysia, was conducted. A validated, self-administered Malay version of the Oldenburg exhaustion Inventory (OLBI-M) was used to assess the level of exhaustion among participants. The average score was used to classify the degree of exhaustion. Using logistic regression, the association between burnouts and socio-demographic profile was examined. Results: With a response rate of 93.5%, a total of 332 individuals were enlisted. Participants with burnout were 29.5% of the total. Factors that was significantly associated with burnout were the position as doctors (AOR 0.24, 95% CI = 0.12, 0.48) and perception of underpaid (AOR=1.85, 95% CI=1.04, 3.31). Conclusion: The current study indicates a lower rate of burnout among healthcare professionals (HCP) compared to prior research findings. Nevertheless, this number holds significance for our purposes. Prioritising the mitigation of burnout among healthcare professionals should be regarded as a crucial imperative for ensuring the sustainable provision of patient care amidst the ongoing epidemic.